If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying lnx + ln(2x + 1) = 0 Reorder the terms: lnx + ln(1 + 2x) = 0 lnx + (1 * ln + 2x * ln) = 0 lnx + (1ln + 2lnx) = 0 Reorder the terms: 1ln + lnx + 2lnx = 0 Combine like terms: lnx + 2lnx = 3lnx 1ln + 3lnx = 0 Solving 1ln + 3lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(1 + 3x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(1 + 3x)' equal to zero and attempt to solve: Simplifying 1 + 3x = 0 Solving 1 + 3x = 0 Move all terms containing l to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 3x = 0 + -1 3x = 0 + -1 Combine like terms: 0 + -1 = -1 3x = -1 Add '-3x' to each side of the equation. 3x + -3x = -1 + -3x Combine like terms: 3x + -3x = 0 0 = -1 + -3x Simplifying 0 = -1 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x-19.8=47.4 | | 4x^2+12x+9=13 | | 3t+5=23 | | 3.54+0.81z=-3.4+8.63z | | -5(3b+2)+(16b-8)=0 | | W+8=2 | | 2x-8y=-24 | | ln(7x+2)=2 | | 4.1+2.9y=-8.88+1.7y | | 2[x-(1-3x)]=3(x+1) | | 4.12+2.9y=8.88+1.74y | | 2.6q-4.1-2.5q=-0.9q-4.9 | | 0=2x^2+6x-80 | | 4x+5y=32 | | 2x^2+6x-80=0 | | 9s^2-64t^2=0 | | 25xY= | | 8(v-5)=9(5+v) | | 0.01z+4.5=5.44-8.51 | | 25c^2+60ct+36t^2=0 | | 001z+4.5=5.44-8.51 | | 7Y-1.3=5 | | A-17=-11 | | -17=-11 | | 5x^3-4x^2+20x-16=0 | | x^1+10x+25=8 | | (x+1)(2x+5)=0 | | 25s^2-90s+81=0 | | R+17=10 | | 19b-14-21b=-2 | | 0.9m+1.2=3 | | -2x+9= |